2018
DOI: 10.3329/dujps.v17i1.37112
|View full text |Cite
|
Sign up to set email alerts
|

Bioactivity Screening of Erechtites valerianifolia (Link Ex Wolf.) Less. Extracts as Antiplasmodium, Antibacterial, Antifungal and Cytotoxic Agents

Abstract: Indonesia's rich natural resources have encouraged many researchers to explore their potential for finding treatment of endemic diseases and malignancy. One of these resources is Erechtites valerianifolia (Link Ex Wolf.) Less. Ex DC or "Jonggolan" (Indonesian name), a member of the family Asteraceae was collected from Meru Betiri Forest. Empirical evidence reveals the use of this plant to treat fever, diarrhea, tonsillitis, wounds, and eczema. A study in 2015 reported that the family Asteraceae passed the test… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 18 publications
0
1
0
Order By: Relevance
“…Erechtites valerianifolius has a caloric value of 29.2 kcal in 100g and high concentrations of β-carotene, K, Ca, Fe and Mg (BARREIRA et al, 2019), in addition to 23% protein content (KINUPP; BARROS, 2008). According to Puspaningtyas et al (2018) this species, which is commonly found in Indonesia, has antioxidant, antifungal, antibacterial, antiplasmodial and cytotoxic activities, and is also used to treat fever, diarrhea, tonsillitis, wounds and eczema.…”
Section: Resultsmentioning
confidence: 99%
“…Erechtites valerianifolius has a caloric value of 29.2 kcal in 100g and high concentrations of β-carotene, K, Ca, Fe and Mg (BARREIRA et al, 2019), in addition to 23% protein content (KINUPP; BARROS, 2008). According to Puspaningtyas et al (2018) this species, which is commonly found in Indonesia, has antioxidant, antifungal, antibacterial, antiplasmodial and cytotoxic activities, and is also used to treat fever, diarrhea, tonsillitis, wounds and eczema.…”
Section: Resultsmentioning
confidence: 99%